A hydration-resistant, corrosion-resistant low-carbon unfired magnesium-calcium carbon brick and a manufacturing method thereof

By using specific ratios of magnesium calcium sand, magnesium sand, graphite and other materials in magnesium calcium carbon bricks, and carrying out waterproofing and high-pressure molding, the problems of hydration and corrosion resistance of magnesium calcium refractory materials are solved, achieving high efficiency The hydration resistance and corrosion resistance are improved, meeting the needs of industrial production.

CN118851729BActive Publication Date: 2024-12-13LIAONING ZHONGMEI HLDG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411319491.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-13
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Magnesium calcium refractory materials are prone to hydration and erosion resistance during production, storage and transportation, resulting in a decrease in the strength and refraction resistance of carbon bricks that do not burn magnesium calcium, and existing improvement measures cannot meet industrial needs.

Method used

Using hydration-resistant, corrosion-resistant low-carbon, non-burning magnesium-calcium carbon bricks, through specific ratios of magnesium-calcium sand, magnesium sand, graphite, nano-titanium diboride, metal silicon powder, anhydrous liquid phenolic resin and environmentally friendly composite carbon The bonding agent, combined with waterproofing treatment and high-pressure molding process, improves the hydration resistance and corrosion resistance of bricks.

Benefits of technology

It significantly improves the hydration resistance and corrosion resistance of magnesium-calcium carbon bricks, extends the service life of the smelting furnace, reduces energy consumption, meets the needs of industrial production, and improves product quality under cost control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the field of refractory materials technology in the field of new materials for smelting or refining furnace linings of special steels such as clean steel, special steel, stainless steel, etc., and specifically relates to a hydration-resistant, corrosion-resistant low-carbon unburned magnesium calcium carbon brick and a manufacturing method thereof. The present invention can improve the hydration resistance of magnesium calcium carbon unburned bricks during mixing, pressing, heating and curing, storage, and transportation, and improve the corrosion resistance of magnesium calcium carbon products, thereby increasing the service life of the smelting furnace, reducing energy consumption, and achieving green production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of refractory materials for new materials used in smelting or refining furnace linings of special steels such as clean steel, special steel and stainless steel, and specifically relates to a hydration-resistant and corrosion-resistant low-carbon unburned magnesium-calcium carbon brick and a manufacturing method thereof. Background Art

[0002] In recent years, with the development of steel smelting technology, more and more clean steel, pure steel and special steel are being smelted, and the refractory materials used for smelting furnace linings are becoming more and more demanding. Through theoretical research and practical experiments on dolomite (magnesium-calcium) refractory materials, it is found that magnesium-calcium materials not only do not pollute molten steel, but can purify molten steel. Therefore, magnesium-calcium refractory materials are the preferred refractory materials for equipment such as refining and smelting clean steel, pure steel, special steel, etc. outside the furnace.

[0003] Although unfired magnesia-calcium carbon bricks have many advantages such as purifying molten steel and good thermal shock resistance, researchers have conducted many experimental studies on how to solve the problems of hydration and corrosion resistance during production, storage and transportation. It is well known to technicians in this industry that CaO in magnesia-calcium refractory products is very active and can react quickly to generate Ca(OH) after contacting water. 2 Therefore, CaO is particularly easy to hydrate; hydration not only causes the decrease of strength and refractoriness of unfired magnesia-calcium carbon bricks, but when hydration is serious, it may even cause cracking and collapse of bricks, resulting in unsightly surface of bricks.

[0004] At present, there are many ways to improve and solve the hydration problem of magnesium-calcium products, which have certain effects, but still cannot meet the needs of enterprises. In order to purify molten steel, extend the life of furnace lining, and reduce the consumption of refractory materials, the present invention provides a hydration-resistant, corrosion-resistant low-carbon unburned magnesium-calcium carbon brick and its manufacturing method to meet the needs of industrial production. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a hydration-resistant and corrosion-resistant low-carbon unfired magnesia-calcium-carbon brick and a manufacturing method thereof, aiming to improve the hydration resistance of the magnesia-calcium-carbon unfired brick during mixing, pressing, heating and curing, storage and transportation, and to improve the corrosion resistance of the magnesia-calcium-carbon products, thereby increasing the service life of the smelting furnace, reducing energy consumption and achieving green production.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions.

[0007] A hydration-resistant and corrosion-resistant low-carbon unburned magnesium-calcium carbon brick, comprising the following raw materials in parts by weight:

[0008] 5-10 parts of 8-5mm magnesia-calcium sand, 20-35 parts of 5-3mm magnesia-calcium sand, 10-25 parts of 3-1mm magnesia-calcium sand, 5-20 parts of 1-0mm magnesia-calcium sand, 10-20 parts of magnesia fine powder ≤0.074mm, 0.5-5 parts of 92-98 graphite, 0.2-0.8 parts of additives, 0.5-2 parts of antioxidants, 2-4 parts of binders, 0.5-2 parts of environmentally friendly composite carbon binders, and 0.1-0.5 parts of curing agents.

[0009] Furthermore, the preparation method of magnesia-calcium sand is as follows: discard low-grade magnesite ore (calcium oxide content greater than 1.5%) and dolomite ore to prepare ore powder according to the requirements of calcium oxide content, press into balls, and then perform electric melting to produce magnesia-calcium sand with different calcium oxide content.

[0010] Furthermore, the physical and chemical indicators of the magnesium calcium sand and magnesium sand are as shown in Table 1.

[0011] Table 1 Physical and chemical indicators of magnesium calcium sand and magnesium sand

[0012]

[0013] Note: % is mass percentage.

[0014] Furthermore, the physical and chemical indicators of the graphite are shown in Table 2.

[0015] Table 2 Physical and chemical indicators of graphite

[0016]

[0017] Note: % is mass percentage.

[0018] Furthermore, the additive is nano titanium diboride (TiB 2 ), nano titanium diboride is more stable than tungsten carbide or silicon nitride when in contact with pure iron, with a melting point of 2930ºC, good oxidation resistance and chemical stability, excellent wear resistance and resistance to liquid metal corrosion.

[0019] Furthermore, the antioxidant is metallic silicon powder (200 mesh, Si mass content greater than 95%) or silicon carbide powder (200 mesh, SiC mass content greater than 95%).

[0020] Furthermore, the binder is anhydrous liquid phenolic resin, and the curing agent is urotropine.

[0021] Furthermore, the preparation method of the environmentally friendly composite carbon binder is: phenolic resin powder, high temperature asphalt powder and carbon black are mixed in a weight ratio of 15 parts: 80 parts: 5 parts, and after mixing evenly, they are loaded into a closed reactor, heated at 350-400°C for 1-2 hours, and then ground into 100 mesh fine powder for standby use.

[0022] Furthermore, the physical and chemical indicators of the composite carbon binder are shown in Table 3.

[0023] Table 3 Physical and chemical indicators of composite carbon binder.

[0024]

[0025] Note: % is mass percentage.

[0026] A method for manufacturing hydration-resistant and corrosion-resistant low-carbon unburned magnesium-calcium carbon bricks, comprising the following steps:

[0027] 1) Raw material preparation: The magnesia calcium sand and magnesia sand raw materials are crushed and sieved by jaw crusher, roll crusher and Raymond mill respectively to produce magnesia calcium sand granular materials with particle sizes of 8~5mm, 5~3mm, 3~1mm and 1~0mm and magnesia sand fine powder with particle size of ≤0.074mm;

[0028] 2) Waterproofing treatment of magnesium calcium sand: The selected raw material magnesium calcium sand particles are soaked in a special waterproofing agent slurry to form a wrapping film, which is then solidified for use;

[0029] 3) Raw material weighing and preparation: weigh all raw materials according to the required weight and accuracy, and put them into the corresponding temporary storage tank;

[0030] 4) Mixing: All weighed raw materials are fed into a high-speed mixer for mixing. The order of adding materials is as follows: first, the magnesium calcium sand with a particle size of 8-5mm, 5-3mm, 3-1mm, and 1-0mm and the magnesium sand fine powder with a particle size of ≤0.074mm in step 2) are mixed for 3-5 minutes, and then the composite carbon binder is added and mixed for 1-3 minutes, and then graphite, hexamethylenetetramine, additives and antioxidants are added and mixed for 1-3 minutes, and then anhydrous liquid phenolic resin is added and mixed for 5-8 minutes. The material is discharged after mixing evenly and reaching the target material temperature;

[0031] 5) Molding: Weigh the specified weight of clay, evenly place it into the mold cavity of the brick press, and mold it under high pressure with a 2500-ton hydraulic press;

[0032] 6) Heating and curing: The formed bricks are stacked on the unfired brick kiln frame and directly heated and cured in the tempering kiln at a curing temperature of 250~300℃;

[0033] 7) Selection, processing and packaging: The unburned magnesia-calcium bricks out of the kiln do not need to be dipped in wax. After cooling, they are sorted, ground, vacuum-packed and then put into the finished product warehouse.

[0034] Furthermore, the special waterproofing agent includes the following raw materials in parts by weight: 10-30 parts of propylene carbonate, 15-40 parts of anhydrous resin, and 30-50 parts of aluminum titanate; the propylene carbonate is heated to 80°C, the anhydrous resin is poured into the propylene carbonate and stirred for 10-15 minutes, and then the aluminum titanate is added and stirred for 10-15 minutes. The mixture is mixed evenly and the temperature is lowered to room temperature to obtain the special waterproofing agent.

[0035] Compared with the prior art, the beneficial effects of the present invention are as follows.

[0036] 1. The additive is nano titanium diboride (TiB 2 ) has a high melting point of 2930ºC, good oxidation resistance and chemical stability, excellent wear resistance and resistance to liquid metal corrosion such as pure iron, which can effectively improve the corrosion resistance of magnesium calcium carbon bricks. Among them, nano titanium diboride (TiB 2 )Oxidation during use to generate TiO 2 and B 2 O 3 The liquid phase is beneficial to inhibit the expansion of the product structure and improve the high-temperature stress of the product. In addition, this liquid phase plays the role of an oxide film at high temperature and improves the oxidation resistance of the product.

[0037] 2. The special waterproofing agent prepared by the present invention is used: first, a dense coating film layer is formed on the surface of the raw materials and auxiliary materials of the magnesium-calcium brick to prevent water from penetrating and thus avoid hydration, and the conventional production is not affected by the season; during the use of the product, a small part of the aluminum titanate in the special waterproofing agent is decomposed into active titanium oxide and aluminum oxide at 1000°C, which adheres to the surface of the magnesium-calcium raw material and quickly melts with calcium oxide to form a sintered dense coating layer with strong hydrophobicity, ensuring that the product has sufficient strength and corrosion resistance when high and low temperatures are alternating during use. In addition, TiO 2 The formation of TiCN and TiC crystal phases in the bonding matrix helps to improve the mechanical, thermal and chemical properties of carbon-bonded refractory materials, thereby improving the high-temperature performance of unfired magnesia-calcium carbon bricks.

[0038] 3. Use magnesium calcium sand produced from low-grade magnesite to improve resource utilization. The calcium oxide and magnesium oxide grains in the magnesium calcium raw material crystal phase are coarse, evenly distributed, and densely combined. Therefore, compared with other sintered magnesium calcium sands, it has a higher volume density. The products produced have good high-temperature volume stability and strong anti-scouring and anti-erosion properties, and relatively high hydration resistance; 98 electrode graphite / 95 graphite / 92 graphite are selected and used, and the amount of graphite added is controlled below 5%, producing high- and medium-grade quality products suitable for use in different parts of high-temperature smelting furnaces, and reducing costs. The excellent hydration resistance and erosion resistance of the unfired magnesium calcium carbon brick runs through the entire process of production and on-site use.

[0039] 4. During the preparation process of the composite carbon binder, harmful impurities such as sulfur and benzanthracene in the asphalt that was previously used alone are removed. As an auxiliary binder, the carbon chain is made flexible, the brittleness problem of the resin-bound carbon chain is solved, the strength of the carbon chain is enhanced, the durability of the product is improved, and it is environmentally friendly.

[0040] 5. Special waterproof magnesium calcium sand is used as aggregate, anhydrous liquid phenolic resin, composite carbon binder, etc. are used as composite binders, and nano titanium diboride (TiB 2 ) additives, with metal silicon or silicon carbide as antioxidants, and then adding an appropriate amount of graphite. The treated magnesium calcium sand aggregate has anti-hydration properties, which ensures the good anti-hydration properties of the pressed brick mud. This anti-hydration effect also plays a role in the pressed bricks and in the low-temperature baking and curing process; after the unfired magnesium calcium carbon bricks are out of the kiln, this synergistic anti-hydration effect still exists, making the finished bricks also have excellent anti-hydration properties.

[0041] 6. The present invention can significantly improve the hydration resistance of unburned magnesia-calcium carbon bricks without significantly increasing costs and complicating the production process, improve the yield in the production process, reduce waste caused by hydration, and extend the shelf life of the finished product under normal packaging conditions.

[0042] The anti-hydration and corrosion-resistant low-carbon unburned magnesia-calcium carbon brick produced by the present invention has excellent anti-hydration performance and corrosion resistance, wherein this excellent anti-hydration property runs through the entire production and use process. Under the premise of using ordinary liquid phenolic resin and magnesia-calcium sand, it can be achieved by maintaining the existing process, and the shelf life reaches more than one year. The additive also improves the corrosion resistance of the product. In general, the manufacturer reduces costs and improves product quality. DETAILED DESCRIPTION

[0043] In order to make those skilled in the art better understand the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. These embodiments should be understood to be only used to illustrate the present invention and not to limit the protection scope of the present invention. After reading the contents recorded in the present invention, all other embodiments obtained after various changes or modifications made to the present invention based on the technical solution and embodiments of the present invention also fall within the scope of protection of the claims of the present invention.

[0044] A hydration-resistant and corrosion-resistant low-carbon unburned magnesium-calcium carbon brick, comprising the following raw materials in parts by weight:

[0045] 5-10 parts of 8-5mm magnesia-calcium sand, 20-35 parts of 5-3mm magnesia-calcium sand, 10-25 parts of 3-1mm magnesia-calcium sand, 5-20 parts of 1-0mm magnesia-calcium sand, 10-20 parts of magnesia fine powder ≤0.074mm, 0.5-5 parts of 92-98 graphite, 0.2-0.8 parts of additives, 0.5-2 parts of antioxidants, 2-4 parts of binders, 0.5-2 parts of environmentally friendly composite carbon binders, and 0.1-0.5 parts of curing agents.

[0046] Furthermore, the preparation method of magnesia-calcium sand is as follows: discard low-grade magnesite ore (calcium oxide content greater than 1.5%) and dolomite ore to prepare ore powder according to the requirements of calcium oxide content, press into balls, and then perform electric melting to produce magnesia-calcium sand with different calcium oxide content.

[0047] Furthermore, the physical and chemical indicators of the magnesium calcium sand and magnesium sand are as shown in Table 1.

[0048] Furthermore, the physical and chemical indicators of the graphite are shown in Table 2.

[0049] Furthermore, the additive is nano titanium diboride (TiB 2 ), nano titanium diboride is more stable than tungsten carbide or silicon nitride when in contact with pure iron, with a melting point of 2930ºC, good oxidation resistance and chemical stability, excellent wear resistance and resistance to liquid metal corrosion.

[0050] Furthermore, the antioxidant is metallic silicon powder (200 mesh, Si mass content greater than 95%) or silicon carbide powder (200 mesh, SiC mass content greater than 95%).

[0051] Furthermore, the binder is anhydrous liquid phenolic resin, and the curing agent is urotropine.

[0052] Furthermore, the preparation method of the environmentally friendly composite carbon binder is: phenolic resin powder, high temperature asphalt powder and carbon black are mixed in a weight ratio of 15 parts: 80 parts: 5 parts, and after mixing evenly, they are loaded into a closed reactor, heated at 350-400°C for 1-2 hours, and then ground into 100 mesh fine powder for standby use.

[0053] Furthermore, the physical and chemical indicators of the composite carbon binder are shown in Table 3.

[0054] A method for manufacturing hydration-resistant and corrosion-resistant low-carbon unburned magnesium-calcium carbon bricks, comprising the following steps:

[0055] 1) Raw material preparation: The magnesia calcium sand and magnesia sand raw materials are crushed and sieved by jaw crusher, roll crusher and Raymond mill respectively to produce magnesia calcium sand granular materials with particle sizes of 8~5mm, 5~3mm, 3~1mm and 1~0mm and magnesia sand fine powder with particle size of ≤0.074mm;

[0056] 2) Waterproofing treatment of magnesium calcium sand: The selected raw material magnesium calcium sand particles are soaked in a special waterproofing agent slurry to form a wrapping film, which is then solidified for use;

[0057] 3) Raw material weighing and preparation: weigh all raw materials according to the required weight and accuracy, and put them into the corresponding temporary storage tank;

[0058] 4) Mixing: All weighed raw materials are fed into a high-speed mixer for mixing. The order of adding materials is as follows: first, the magnesium calcium sand with a particle size of 8-5mm, 5-3mm, 3-1mm, and 1-0mm and the magnesium sand fine powder with a particle size of ≤0.074mm in step 2) are mixed for 3-5 minutes, and then the composite carbon binder is added and mixed for 1-3 minutes, and then graphite, hexamethylenetetramine, additives and antioxidants are added and mixed for 1-3 minutes, and then anhydrous liquid phenolic resin is added and mixed for 5-8 minutes. The material is discharged after mixing evenly and reaching the target material temperature;

[0059] 5) Molding: Weigh the specified weight of clay, evenly place it into the mold cavity of the brick press, and mold it under high pressure with a 2500-ton hydraulic press;

[0060] 6) Heating and curing: The formed bricks are stacked on the unfired brick kiln frame and directly heated and cured in the tempering kiln at a curing temperature of 250~300℃;

[0061] 7) Selection, processing and packaging: The unburned magnesia-calcium bricks out of the kiln do not need to be dipped in wax. After cooling, they are sorted, ground, vacuum-packed and then put into the finished product warehouse.

[0062] Furthermore, the special waterproofing agent includes the following raw materials in parts by weight: 10-30 parts of propylene carbonate, 15-40 parts of anhydrous resin, and 30-50 parts of aluminum titanate; the propylene carbonate is heated to 80°C, the anhydrous resin is poured into the propylene carbonate and stirred for 10-15 minutes, and then the aluminum titanate is added and stirred for 10-15 minutes. The mixture is evenly mixed and the temperature is lowered to room temperature to obtain the special waterproofing agent.

[0063] Example 1.

[0064] A hydration-resistant and corrosion-resistant low-carbon unburned magnesium-calcium carbon brick, which is made of the following raw materials in proportion by weight:

[0065] 5 parts of 8~5mm magnesia calcium sand, 34 parts of 5~3mm magnesia calcium sand, 25 parts of 3~1mm magnesia calcium sand, 5 parts of 1~0mm magnesia calcium sand, 18 parts of magnesia sand fine powder ≤0.074mm, 0.5 parts of 98 electrode graphite, 0.8 parts of additive nano titanium diboride, 0.5 parts of antioxidant metal silicon powder, 2 parts of anhydrous liquid phenolic resin, 2 parts of composite carbon binder, and 0.1 parts of urotropine; the magnesia calcium sand is waterproofed.

[0066] The physical and chemical indicators of the magnesium calcium sand used in this embodiment are shown in Table 4.

[0067] Table 4 Physical and chemical indicators of magnesium calcium sand

[0068]

[0069] Note: % is mass percentage.

[0070] The physical and chemical indicators of the graphite used in this embodiment are shown in Table 5.

[0071] Table 5 Physical and chemical indicators of graphite

[0072]

[0073] Note: % is mass percentage.

[0074] The physical and chemical indicators of the magnesia sand used in this embodiment are shown in Table 1, and the physical and chemical indicators of the composite carbon binder are shown in Table 3.

[0075] The manufacturing method of the above-mentioned hydration-resistant and corrosion-resistant low-carbon unfired magnesia-calcium carbon brick comprises the following steps:

[0076] 1) Raw material preparation: The magnesia calcium sand and magnesia sand raw materials are crushed and sieved by jaw crusher, roll crusher and Raymond mill respectively to produce magnesia calcium sand granular materials with particle sizes of 8~5mm, 5~3mm, 3~1mm and 1~0mm and magnesia sand fine powder with particle size of ≤0.074mm;

[0077] 2) Waterproofing treatment of magnesium calcium sand: The selected raw material magnesium calcium sand particles are respectively soaked in a special waterproofing agent slurry to form a wrapping film, which is solidified and set aside; the special waterproofing agent is composed of 30 parts of propylene carbonate, 35 parts of anhydrous resin, and 35 parts of aluminum titanate; the propylene carbonate is heated to 80°C, the anhydrous resin is poured into the propylene carbonate and stirred for 10 minutes, and then the aluminum titanate is added and stirred for 15 minutes, mixed evenly, and the temperature is reduced to room temperature to obtain the special waterproofing agent;

[0078] 3) Raw material weighing and preparation: weigh all raw materials according to the required weight and accuracy, and put them into the corresponding temporary storage tank;

[0079] 4) Mixing: All weighed raw materials are fed into a high-speed mixer for mixing. The order of adding materials is as follows: first, the magnesium calcium sand with a particle size of 8-5mm, 5-3mm, 3-1mm, and 1-0mm and the magnesium sand fine powder with a particle size of ≤0.074mm in step 2 are mixed for 3-5 minutes, and then the composite carbon binder is added and mixed for 1-3 minutes, and then graphite, hexamethylenetetramine, additives and antioxidants are added and mixed for 1-3 minutes, and then anhydrous liquid phenolic resin is added and mixed for 5-8 minutes. After mixing evenly and reaching the target material temperature, the material is discharged;

[0080] 5) Molding: Weigh the specified weight of clay, evenly place it into the mold cavity of the brick press, and mold it under high pressure with a 2500-ton hydraulic press;

[0081] 6) Heating and curing: The formed bricks are stacked on the unfired brick kiln frame and directly heated and cured in the tempering kiln at a curing temperature of 250~300℃;

[0082] 7) Selection, processing and packaging: The unburned magnesia-calcium bricks out of the kiln do not need to be dipped in wax. After cooling, they are sorted, ground, vacuum-packed and then put into the finished product warehouse.

[0083] The test results of the finished product of this embodiment are shown in Table 11.

[0084] Example 2.

[0085] The hydration-resistant and corrosion-resistant low-carbon unburned magnesium-calcium carbon brick is made of the following raw materials in proportion by weight:

[0086] 8 parts of 8~5mm magnesia calcium sand, 20 parts of 5~3mm magnesia calcium sand, 24 parts of 3~1mm magnesia calcium sand, 10 parts of 1~0mm magnesia calcium sand, 20 parts of magnesia sand fine powder ≤ 0.074mm, 5 parts of 92 graphite, 0.5 parts of additive nano titanium diboride, 2 parts of antioxidant metal silicon powder, 4 parts of anhydrous liquid phenolic resin, 0.5 parts of composite carbon binder, and 0.5 parts of urotropine; the magnesia calcium sand is waterproofed.

[0087] The physical and chemical indicators of the magnesium calcium sand used in this embodiment are shown in Table 6.

[0088] Table 6 Physical and chemical indicators of magnesium calcium sand

[0089]

[0090] Note: % is mass percentage.

[0091] The physical and chemical indicators of the graphite used in this embodiment are shown in Table 7.

[0092] Table 7 Physical and chemical indicators of graphite

[0093]

[0094] Note: % is mass percentage.

[0095] The physical and chemical indicators of magnesia are shown in Table 1, and the physical and chemical indicators of composite carbon binder are shown in Table 3.

[0096] The manufacturing method of the hydration-resistant and corrosion-resistant low-carbon unburned magnesium-calcium carbon brick has the same process steps as those described in Example 1. The test results of the finished product of this example are shown in Table 11.

[0097] Example 3.

[0098] The hydration-resistant and corrosion-resistant low-carbon unburned magnesium-calcium carbon brick is made of the following raw materials in proportion by weight:

[0099] 10 parts of 8~5mm magnesia calcium sand, 35 parts of 5~3mm magnesia calcium sand, 10 parts of 3~1mm magnesia calcium sand, 20 parts of 1~0mm magnesia calcium sand, 10 parts of magnesia sand fine powder ≤ 0.074mm, 4 parts of 95 graphite, 0.5 parts of additive nano titanium diboride, 1 part of antioxidant metal silicon powder, 3 parts of anhydrous liquid phenolic resin, 1 part of composite carbon binder, and 0.2 parts of urotropine; the magnesia calcium sand is waterproofed.

[0100] The physical and chemical indicators of the magnesium calcium sand used in this embodiment are shown in Table 8.

[0101] Table 8 Physical and chemical indicators of magnesium calcium sand

[0102]

[0103] Note: % is mass percentage.

[0104] The physical and chemical indicators of the graphite used in this embodiment are shown in Table 9.

[0105] Table 9 Physical and chemical indicators of graphite

[0106]

[0107] Note: % is mass percentage.

[0108] The physical and chemical indicators of magnesia are shown in Table 1, and the physical and chemical indicators of composite carbon binder are shown in Table 3.

[0109] The manufacturing method of the above-mentioned hydration-resistant and corrosion-resistant low-carbon unburned magnesia-calcium carbon brick has the same process steps as the process steps described in Example 1. The test results of the finished product of this example are shown in Table 11.

[0110] Comparative Example 1 (conventional magnesium calcium carbon brick).

[0111] Traditional unburned magnesium calcium carbon bricks are made of the following raw materials in proportion by weight:

[0112] 8 parts of 8~5mm magnesia calcium sand, 32 parts of 5~3mm magnesia calcium sand, 25 parts of 3~1mm magnesia calcium sand, 8 parts of 1~0mm magnesia calcium sand, 7 parts of 1~0mm magnesia sand, 10 parts of magnesia sand ≤0.074mm, 5 parts of 95 graphite, 1.5 parts of antioxidant metal silicon powder, 3 parts of anhydrous liquid phenolic resin, 0.1 parts of urotropine, and 0.5 parts of high-temperature asphalt powder; the magnesia calcium sand has not been waterproofed.

[0113] The physical and chemical indicators of magnesium calcium sand are shown in Table 4, the physical and chemical indicators of magnesium sand are shown in Table 1, and the physical and chemical indicators of 95 graphite are shown in Table 9.

[0114] Table 10 Physical and chemical indicators of high temperature asphalt powder

[0115]

[0116] Note: % is mass percentage.

[0117] The manufacturing method of the traditional unfired magnesium calcium carbon brick is as follows:

[0118] 1) Raw material preparation: The magnesia calcium sand and magnesia sand raw materials are crushed and sieved by jaw crusher, roll crusher and Raymond mill respectively to produce magnesia calcium sand granular materials with particle sizes of 8~5mm, 5~3mm, 3~1mm and 1~0mm and magnesia sand materials with particle sizes of 1~0mm and ≤0.074mm;

[0119] 2) Raw material weighing and preparation: weigh all raw materials according to the required weight and accuracy, and put them into the corresponding temporary storage tank;

[0120] 3) Mixing: All weighed raw materials are fed into a high-speed mixer for mixing. The order of adding materials is as follows: first, the magnesium calcium sand with a particle size of 8~5mm, 5~3mm, 3~1mm, 1~0mm and the magnesium sand with a particle size of 1~0mm and ≤0.074mm in step 1) are mixed for 3~5 minutes, and then high-temperature asphalt powder is added and mixed for 1~3 minutes, and then 95 graphite, hexamethylenetetramine and antioxidant metal silicon powder are added and mixed for 1~3 minutes, and then anhydrous liquid phenolic resin is added and mixed for 5~8 minutes. After mixing evenly and reaching the target material temperature, the material is discharged;

[0121] 4) Molding: Weigh the specified weight of clay, evenly place it into the mold cavity of the brick press, and mold it under high pressure with a 2500-ton hydraulic press;

[0122] 5) Heating and curing: The formed bricks are stacked on the unfired brick kiln frame and directly heated and cured in the tempering kiln at a curing temperature of 250~300℃;

[0123] 6) Selection, processing and packaging: The unburned magnesia-calcium bricks out of the kiln are dipped in wax, cooled, and then sorted, ground, vacuum-packed, and put into the finished product warehouse.

[0124] The test results of the finished product of this comparative example are shown in Table 11.

[0125] Table 11 Physical and chemical indicators of finished products of various embodiments and comparative examples

[0126]

[0127] Note: The % of apparent porosity is volume percentage, and the remaining % is mass percentage.

[0128] Comparative Example 1-In the traditional production process of magnesium-calcium-carbon bricks, the raw material particles are not waterproofed and need to be waxed after drying. Due to the uneven waxing, hydration often occurs during the storage and transportation of the products, resulting in quality fluctuations and a storage period of three months.

[0129] Compared with comparative example 1, the shelf life of the products of examples 1, 2 and 3 is extended by 9 months, which can meet the production use cycle. From the perspective of physical and chemical indicators, both the room temperature strength and the high temperature strength are improved, and the service life of the products in actual use is increased by 15%.

Claims

1. A method for manufacturing hydration-resistant and corrosion-resistant low-carbon unburned magnesium-calcium-carbon bricks, characterized in that: The steps include: 1) Raw material preparation: The magnesia calcium sand and magnesia sand raw materials are crushed and sieved by jaw crusher, roll crusher and Raymond mill respectively to produce magnesia calcium sand granular materials with particle sizes of 8~5mm, 5~3mm, 3~1mm and 1~0mm and magnesia sand fine powder with particle size of ≤0.074mm; 2) Waterproofing treatment of magnesium calcium sand: The selected raw material magnesium calcium sand particles are soaked in a special waterproofing agent slurry to form a wrapping film, which is solidified for use; the special waterproofing agent includes the following raw materials in parts by weight: 10-30 parts of propylene carbonate, 15-40 parts of anhydrous resin, and 30-50 parts of aluminum titanate; the propylene carbonate is heated to 80°C, the anhydrous resin is poured into the propylene carbonate and stirred for 10-15 minutes, and then the aluminum titanate is added and stirred for 10-15 minutes, and the mixture is evenly mixed, and the temperature is reduced to room temperature to obtain the special waterproofing agent; 3) Raw material weighing and preparation: weigh all raw materials according to the required weight and accuracy, and put them into the corresponding temporary storage tank; 4) Mixing: All weighed raw materials are fed into a high-speed mixer for mixing. The order of adding materials is as follows: first, the magnesium calcium sand with a particle size of 8-5mm, 5-3mm, 3-1mm, and 1-0mm and the magnesium sand fine powder with a particle size of ≤0.074mm in step 2) are mixed for 3-5 minutes, and then the environmentally friendly composite carbon binder is added and mixed for 1-3 minutes, and then graphite, hexamethylenetetramine, additives and antioxidants are added and mixed for 1-3 minutes, and then anhydrous liquid phenolic resin is added and mixed for 5-8 minutes. The material is discharged after mixing evenly and reaching the target material temperature; 5) Molding: Weigh the specified weight of clay, evenly place it into the mold cavity of the brick press, and mold it under high pressure with a 2500-ton hydraulic press; 6) Heating and curing: The formed bricks are stacked on the unfired brick kiln frame and directly heated and cured in the tempering kiln at a curing temperature of 250~300℃; 7) Selection, processing and packaging: The unburned magnesia-calcium bricks out of the kiln do not need to be dipped in wax. After cooling, they are sorted, ground, vacuum-packed and put into the finished product warehouse; The hydration-resistant and corrosion-resistant low-carbon unburned magnesia-calcium carbon brick comprises the following raw materials in parts by weight: 5-10 parts of 8-5mm magnesium calcium sand, 20-35 parts of 5-3mm magnesium calcium sand, 10-25 parts of 3-1mm magnesium calcium sand, 5-20 parts of 1-0mm magnesium calcium sand, 10-20 parts of ≤0.074mm magnesium sand fine powder, 0.5-5 parts of 92-98 graphite, 0.2-0.8 parts of additives, 0.5-2 parts of antioxidants, 2-4 parts of binders, 0.5-2 parts of environmentally friendly composite carbon binders, and 0.1-0.5 parts of curing agents; The additive is nano titanium diboride; The preparation method of the environmentally friendly composite carbon binder is as follows: phenolic resin powder, high-temperature asphalt powder and carbon black are mixed in a weight ratio of 15 parts: 80 parts: 5 parts, and after mixing evenly, they are loaded into a closed reactor, heated at 350-400°C for 1-2 hours, and then ground into 100 mesh fine powder for standby use.

2. The method for manufacturing the hydration-resistant and corrosion-resistant low-carbon unburned magnesia-calcium-carbon brick according to claim 1, characterized in that: The preparation method of magnesia-calcium sand is as follows: waste low-grade magnesite ore and dolomite ore are prepared into ore powder according to the requirements of calcium oxide mass content, and then the ore powder is pressed into balls and then subjected to electric melting to produce magnesia-calcium sand with different calcium oxide mass contents.

3. The method for manufacturing the hydration-resistant and corrosion-resistant low-carbon unburned magnesia-calcium-carbon brick according to claim 1, characterized in that: The antioxidant is 200 mesh metal silicon powder with Si mass content greater than 95% or 200 mesh silicon carbide powder with SiC mass content greater than 95%.

4. The method for manufacturing the hydration-resistant and corrosion-resistant low-carbon unburned magnesia-calcium carbon brick according to claim 1, characterized in that: The binder is anhydrous liquid phenolic resin, and the curing agent is urotropine.